Highly Reversible Cycling of Zn‐MnO2 Batteries Integrated with Acid‐Treated Carbon Supportive Layer. Issue 2 (2nd December 2021) - Kim, Byung Gon; Park, Sang Wook; Choi, Hong Jun; Park, Jun‐Woo; Lee, Hongkyung; Choi, Jeong‐Hee
Abstract: Zn‐MnO2 battery with mild‐acid electrolytes has been considered as a promising alternative to Li‐ion battery for safe and cost‐effective energy storage systems (ESSs), and for full electrification. However, the governing mechanism of MnO2 electrochemistry has not been fully elucidated, hindering further advances in highly reversible MnO2 cathodes. Eventual Mn 2+ ion dissolution into the electrolyte adversely triggers the irreversible loss of Mn 2+ ions and the excessive precipitation of zinc hydroxyl sulfate (Zn4 SO4 (OH)6 · x H2 O, ZHS), leading to irreversible capacity loss upon prolonged cycling. To overcome these drawbacks, a rationally renovated cell structure is proposed by integrating an acid‐treated carbon supportive layer (aCSL) in the MnO2 cathode, which can play multifunctional roles rendering the additional reaction sites for the reversible formation/decomposition of ZHS and re‐utilization of the dissolved Mn 2+ ions. Furthermore, the improved affinity of the aCSL toward the electrolyte is beneficial for increasing active surface area and facilitating charge transfer at the cathode side. Benefiting from these features, compared to the conventional cell configuration, the aCSL‐integrated Zn‐MnO2 cell exhibits superior cycling over 3000 cycles with negligible capacity decay (85.6% retention) at a current of 3 A g −1 . Abstract : Compared to the Zn‐MnO2 cell with a common porous separator showing gradual capacity decay during cycling, the cell incorporating an acid‐treated carbon support layer (aCSL) shows better cycle and rate performances, owing to confinement of Mn 2+ between cathode and aCSL, revitalization of Mn 2+ /Mn 4+ reactions, and facilitation of zinc hydroxyl sulfate formation/decomposition by rendering extra e‐pathway, resulting in robust cycling of the Zn‐MnO2 cell.